It's not what it looks like: molecular data fails to substantiate morphological differences in two sea hares (Mollusca, Heterobranchia, Aplysiidae) from southern Brazil - Saad, Luiza de Oliveira [UNESP]; Cunha, Carlo Magenta; Delevati Colpo, Karine; Valdes, Angel (Springer, 2014)
Species of sea hares have been recognized traditionally based on morphological traits, mainly the radula, external coloration, and reproductive anatomy. However, recent studies have shown substantial color variation in some sea slug species. Molecular data have been successfully used to differentiate morphologically similar species of "opisthobranchs'' and resolve questions on the taxonomic value of color. The objective of this paper is to use molecular data in an attempt to elucidate whether specimens of Aplysia brasiliana with distinct colorations and morphologies are actually the same species. To this end, DNA from 14 specimens of A. brasiliana was extracted, including five specimens identified as a distinct morphotype from typical A. brasiliana. Although the two morphotypes have consistent differences in their external morphology and radula, the molecular data confirmed that there are no significant genetic differences between them. This is another example of the need to re-evaluate taxonomic decisions based on morphology in light of molecular evidence.
Keywords: Aplysia; CO1; 16S; Morphological variation